2013
DOI: 10.1111/tran.12011
|View full text |Cite
|
Sign up to set email alerts
|

Seeing power in international development cooperation: environmental policy integration and the World Bank

Abstract: The aim of this paper is to sharpen the ways in which power dynamics can be analytically 'seen' in complex governance contexts where particular ways of governing, and their associated horizons of thought, shape and are in turn shaped by intricate interactions between actors. A theoretical approach is proposed, combining a governmentality perspective with Stewart Clegg's theory of circuits of power. The framework is applied in a case study of experimentation by the World Bank with a new tool for Environmental P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(37 reference statements)
0
10
0
1
Order By: Relevance
“…The concept of SEA, however, dates back to the 1969 United States National Environmental Policy Act (NEPA), which required an environmental assessment of proposed federal legislation (Fundingsland Tetlow and Hanusch , p. 15). Given the similarity between EIA and SEA, the 1969 NEPA is also seen as the origin of EIA (see Cashmore et al , p. 157). In 2003, the EU adopted the SEA Protocol to the Espoo Convention, which introduces a non‐mandatory application of SEA to policies and legislation in addition to public plans and programmes (Fundingsland Tetlow and Hanusch , p. 17).…”
Section: Origins Concept and The Design Of Tools For Environmental Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of SEA, however, dates back to the 1969 United States National Environmental Policy Act (NEPA), which required an environmental assessment of proposed federal legislation (Fundingsland Tetlow and Hanusch , p. 15). Given the similarity between EIA and SEA, the 1969 NEPA is also seen as the origin of EIA (see Cashmore et al , p. 157). In 2003, the EU adopted the SEA Protocol to the Espoo Convention, which introduces a non‐mandatory application of SEA to policies and legislation in addition to public plans and programmes (Fundingsland Tetlow and Hanusch , p. 17).…”
Section: Origins Concept and The Design Of Tools For Environmental Pmentioning
confidence: 99%
“…The literature has attributed to the WB a significant role in the diffusion of EIA (see Busch and Jörgens ) and SEA (see Fundingsland Tetlow and Hanusch ; Cashmore et al ). Has the EU served as a model for the WB's approach to EIA and/or SEA?…”
Section: International Organizations and Environmental Policy Integramentioning
confidence: 99%
“…We have suggested that the substantial investment made by the World Bank in delineating Policy SEA from other IA practices was linked to the way the organization maintains its position internationally. The delineation of Policy SEA as something new buttresses claims that the organization holds privileged, cutting-edge knowledge on development issues (Cashmore et al 2013).…”
Section: On the Call For Unificationmentioning
confidence: 99%
“…In Brazil for example, SEA is commonly being used voluntarily or as part of loan schemes (PELLIN et al, 2011). In this latter context, MDAs are considered major players in the SEA practice, once it has become a standard tool used in the preparation and implementation of Bank-financed development projects to safeguard environmental interests and contribute to environmental governance (ALSHWAIKHAT, 2005;CASHMORE, 2011;AXELSSON, 2013;CASHMORE et al, 2014).…”
Section: Strategic Environmental Assessment: Principles and Conceptuamentioning
confidence: 99%
“…According to interviewee #6 (consultant), without a legal framework, SEA is systematically required only by MDAs, and randomly required by private companies, state or federal governments. SEA is part of the funding policy of a MDA and is meant to safeguard environmental interests and contribute to environmental governance (RICHARDSON; CASHMORE, 2011;AXELSSON, 2013;CASHMORE et al, 2014). Regarding private initiatives, society and governments, SEA is applied when there is not any other option, mostly when EIA could not support PPPs decision-making.…”
Section: (I) Lack Of Sea Regulations and Guidancementioning
confidence: 99%